Peran Media Iklan Televisi Sebagai Media Kritik Sosial Kasus Korupsi (Studi Kasus Pada Iklan Djarum 76 Versi “Kontes Jin”) - Ita Suryani (Jurnal Komunikasi, 2015)
Corruption should be viewed as an extraordinary crime, are therefore also require tremendous efforts to eradicate it. Efforts to combat corruption which is composed of two major parts, namely (1) the prosecution, and (2) prevention -not will never work optimally if it is only done by government alone without involving the participation to people's media industry. Therefore, advertising media can be used as an important part that can act as a medium of social criticism on the issue of corruption in Indonesia.Djarum 76 for example, ads Djarum 76 as we know it often featured social themes which then can be understood as a form of social criticism. By generating genie figure in each advertisement, Djarum 76 trying to tell its products as manufacturers concentrated on social issues. Image that emerges from these ads is Djarum 76 care social problems that exist, which is then displayed in the form of parody, but full of meaning and social criticism.The method used in this study is case study method which is a research method that uses a variety of data sources that can be used to examine, comprehensively describe and explain the various aspects of individual, group, program, organization or event systematically.The conclusion shows that overall this ad is a form of social criticism that talks about corruption. The elimination of corruption cases were warmly welcomed by everyone who is represented by the audience. However, there is an allusion encountered, which is waiting for the appearance of the genie to resolve corruption cases. Satire is focused on the relevant parties are in fact not able to investigate all cases of corruption. One case took a long time to be completed, while a genie completed all in the blink of an eye.